Influence of Poly-(L-Lactic Acid) Nanofiber Functionalization on Maximum Load, Young's Modulus, and Strain of Nanofiber Scaffolds Before and After Cultivation of Osteoblasts: An In Vitro Study - Jürgen Paletta; Karla Erffmeier; Christina Theisen; Daniel Hussain; Joachim H. Wendorff; Andreas Greiner; Susanne Fuchs-Winkelmann; Markus D. Schofer (The Scientific World Journal)
The aim of this study was to characterize the influence of functionalization of synthetic poly-(L-lactic acid) (PLLA) nanofibers on mechanical properties such as maximum load, elongation, and Young's modulus. Furthermore, the impact of osteoblast growth on the various nanofiber scaffolds stability was determined. Nanofiber matrices composed of PLLA, PLLA-collagen, or BMP-2–incorporated PLLA were produced from different solvents by electrospinning. Standardized test samples of each nanofiber scaffold were subjected to failure protocol before or after incubation in the presence of osteoblasts over a period of 22 days under osteoinductive conditions. PLLA nanofibers electrospun from hexafluoroisopropanol (HFIP) showed a higher strain and tended to have increased maximum loads and Young's modulus compared to PLLA fibers spun from dichloromethane. In addition, they had a higher resistance during incubation in the presence of cells. Functionalization by incorporation of growth factors increased Young's modulus, independent of the solvent used. However, the incorporation of growth factors using the HFIP system resulted in a loss of strain. Similar results were observed when PLLA was blended with different ratios of collagen. Summarizing the results, this study indicates that different functionalization strategies influence the mechanical stability of PLLA nanofibers. Therefore, an optimization of nanofibers should not only account for the optimization of biological effects on cells, but also has to consider the stability of the scaffold.